(3JKbja GdJYQja HGdeUWdM GdTQjas - (3CMeO Hf eMeO GdeUQjs
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi eRjO EfYGeI hfhGdg agPg hQbGJ hVYJgG dhdOi CMeO cGJH GdOQL GdTQja JTJed Ydi GdecGJHGJ GdUGOQI Yf GdehGba GdTQjaI GdSdWGfjI s
(3BNQgG (B:s
(3GdJYQja eMeO Hf GdTgjO GHf SYO GdOjf MGce HdGO GdMHTI s
(3HBNQgG hbaI cGJH hfbhd eNJdaIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B226s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs